STUDY ON RELATIONSHIP BETWEEN AGRONOMIC CHARACTERS AND FARMING VALUE IN SOYBEAN VARIETIES ASSESSMENT - Kustanto, Heri; Khanifah; Amiroh, Ana; Tambu, Teddy; Lazuardi, Mohamad Heru (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2023)
Soybean is important commodity because it is consumed by the whole communities. Soybean plays important role in national food security. In fact, the needs for soybeans currently still depend on import of soybean seeds. The stakeholders and communities have made some efforts to increase soybeans production, and one of them is providing superior and high-qualified varieties, as well as profitable for farming. Objective of the study was to know relationship between agronomic characters and economic values in soybean varieties assessment. The study was to analyze the farming of new superior varieties in comparison with local superior varieties by applying different dose of fertilizer. Furthermore, the research was carried out to look for superiorities of the varieties before they are released. Conclusions of the research are (1) the harvest yield per hectare showed that the treatment of YS2 and YS3 have the highest yields with average values 2.4 and 2.2 tons/ha, respectively. (2) The highest farming income was derived from the treatment of YS0, (3) Extra expenses for farming which were expended for both varieties of Yasi 6 and Grobogan will be able to increase the harvest yield but could not afford to raise income, (4) Yasi 6 could be cultivated in accordance with the farmers’ habits and will be able to raise income.